2018
DOI: 10.1186/s41938-018-0045-0
|View full text |Cite
|
Sign up to set email alerts
|

Orius albidipennis (Rueter) as an effective biocontrol agent against Tetranychus urticae Koch on pepper crops in greenhouse in Egypt

Abstract: The present study was carried out in greenhouses, on sweet pepper crops, during the winter plantations 2015-2016 and 2016-2017 in a commercial farm located at Berkash district, Giza, Egypt. During the first season, three acariphagous biocontrol agent species, the predatory mite, Amblyseius swirskii Athias-Henriot (Acari: Phytoseiidae) (at a rate of 2 individuals/m 2), and two of predatory insect, Macrolophus caliginosus Wagner (at a rate of 1 individual/m 2) and Orius albidipennis (Reuter) (at a rate of 1/2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The land area devoted to greenhouses production of color sweet peppers has been increased substantially over the past decade. In Egypt, it reached 400 ha with total plant-houses area of 11,300 ha (El Arnaouty et al 2018). Also, pepper production is affected by different environmental and management systems, where it ranged from 5 to 28.8 kg/m 2 and export percentage ranged from 50 to 90%.…”
Section: Introductionmentioning
confidence: 99%
“…The land area devoted to greenhouses production of color sweet peppers has been increased substantially over the past decade. In Egypt, it reached 400 ha with total plant-houses area of 11,300 ha (El Arnaouty et al 2018). Also, pepper production is affected by different environmental and management systems, where it ranged from 5 to 28.8 kg/m 2 and export percentage ranged from 50 to 90%.…”
Section: Introductionmentioning
confidence: 99%
“…The highest reduction percentage (79.27 per cent) was obtained after releasing H. convergens at a rate of one adult predator per 73 prey individuals. El-Arnaouty et al (2000) studied the effect of releasing Harmonia axyridis (larvae and adults), for the biological control of the cowpea aphid A. craccivora (3 rd instar predator larvae were released at 1/30 and 1/50 aphid individuals). Results showed that the predator H. axyridis was able to control the aphid species and the best rate of release was 1 predator / 30 aphids/faba bean plant.…”
Section: Pooled Resultsmentioning
confidence: 99%
“…persimilis during two seasons on sweet pepper that gave the highest reduction percentage in population of T. urticae movable stages, but a low reduction in egg populations, while N. californicus preferred T. urticae eggs than movable stages. El-Arnaouty et al (2018) and Taghizadeh et al (2018) stated that O. albidipennis exhibited suitable efficacy on T. urticae stages.…”
Section: All Plant Growth Stagesmentioning
confidence: 98%
“…had promising control capacities especially as Orius albidipennis in Mediterranean countries (Al-Kherb, 2013). The biological control using of O. albidipennis was the most effect bio-agent method against T. urticae under greenhouse conditions, which increased about 31.36% in yield, food safety, and reduce the environmental pollution (El-Arnaouty et al, 2018). On the other hand, Azadirachtin act as a bio-agent, which isolated from Neem tree seeds, Azadirachta indica (Meliaceae) (Sundaram, 1996).…”
Section: Introductionmentioning
confidence: 99%